The Eucharist and the Ministerial Priesthood a Reply to Kenneth Collins and Jerry Walls - Lee Patrick (Perichoresis: The Theological Journal of Emanuel University, 2020)
In chapters 9 and 10 of their book Roman but Not Catholic, Kenneth Collins and Jerry Walls criticize the Roman Catholic positions on the Eucharist as a sacrifice and on the ministerial priesthood. I reply to their historical and theological objections, and defend the belief that the Eucharistic sacrifice, the Mass, is a re-presentation, or making present, of Jesus’s redemptive sacrifice on Calvary, and a key component in God’s incarnational strategy for redeeming us.